CULTURE IN DA'WA WALI SONGO - Abdul Mujib (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
The growth and development of Islam in the early period marked the findings of the tomb of Nisan Fatimah binti Maemun (died 1082 A.D.), in Leran, Gresik, East Java. Estafeta Da'wa Islamiyah unrelenting until the change of the birth of a number of reliable figures, among others, Wali Songo, they are Maulana Malik Ibrahim in Gresik, Sunan Ampel in Surabaya, Sunan Giri in Gresik, Sunan Bonang in Tuban, Sunan Drajat in Lamongan, Sunan Kudus in Kudus, Sunan Muria in Kudus, Sunan Kalijaga in Kadilangu Demak, and Sunan Gunung Jati in Cirebon. The great success of Da'wa Islamiyah has given such an example in the economic aspects. Through economic strength, Islam in Java Island emerged to give birth to political power in the form of Demak Sultanate. The presence of Demak Sultanate is not separated from the role of Wali Songo which is considered as the leader of a large number of Islamic Muballigh in Da'wa Islamiyah in areas in the island of Java.